Extensive characterization of COVID-19 convalescent plasma from Bulgarian donors - Vancho Donev; Yana Todorova; Radoslava Emilova; Georgi Nikolov; Maria Nikolova (Biotechnology & Biotechnological Equipment)
The total and SARS-CoV-2-specific antibody content in convalescent plasma (CP) samples from Bulgarian donors and their therapeutic potential for COVID-19 patients was subjected to characterization. CPs (n = 90) were obtained after informed consent at National Centre of Transfusion Hematology in Sofia, Bulgaria, in the period 01 June 2021 and were tested for RBD-IgG, RBD-IgA and anti-nuclear antibodies (ANA) by semi-quantitative ELISA. Concentrations of total IgG, IgG isotypes, IgA, and IgM, as well as of 25 Th1, Th2, Th17 and regulatory cytokines were determined for all samples; concentrations of Neutralizing antibodies against six SARS-CoV-2 variants were determined in Receptor-Binding Domain (RBD-positive) samples (Luminex xMAP technology). Concordant production of RBD-specific IgG and IgA was detected in 45 (50%); 12 (13.3%) were RBD-IgG single-positive, 8 (8.8%) RBD-IgA single-positive, and 25 (27.7%) – double negative. Absence of neutralizing activity was documented for 8/65 (12.3%) of RBD-positive samples. No correlation existed between the levels of RBD-IgG and RBD-IgA and the total neutralizing activity of CPs (p > 0.05). Total IgG, IgA, IgM and IgG Isotype concentrations did not differ from reference values. Increased concentrations of IL-18, IL-27, IL-1Ra, IL-21 and IL-22 were detected in most tested samples (80% respectively). The comparison between 45 RBD-double positive and 25 RBD-double negative CPs showed significant differences for the concentrations of IL-22 (2.4 vs 40, p < 0.05) and IL-10 (1 vs 15, p < 0.001). All CPs were ANA negative. Detailed characterization for SARS-CoV-2 specific antibody content and cytokine concentrations might improve the results of CPs application for in early stage treatment in resource-limited settings.